KARAKTERISASI DAN KLASIFIKASI TANAH ULTISOL DI KECAMATAN INDRAJAYA KABUPATEN PIDIE - sri Handayani; Karnilawati Karnilawati (Universitas Lancang Kuning, 2018)
This study aims to examine the characteristics of Ultisol soil and produce a system of naming Ultisol soil according to the USDA Land Taxonomy system in Indrajaya District, Pidie District. This research will be carried out in the villages of Gle Gapui, Tuha Suwiek and Masjid Suwiek Indrajaya sub-districts from June to November 2015. This study uses descriptive-quantitative method, which consists of the following stages: (1) Preparation, ie collecting secondary data such as climate data, maps etc. Then prepare the tools and materials for the field survey and establish the ground pedon (2) Field activities, including observation of soil profile, soil sampling, laboratory analysis. Subsequently classified the land based on the USDA Land Taxonomy System Profile Gle Gapui climber determinant (horate Bt) textured clay where there is increasing clay so it is included into the horizontal horizon. Content weight value is inversely proportional to permeability and porosity. The soil reaction is directly proportional to the saturation of base which is equally low. The content of C- organic, P is available and N total is low. Moderate Cation Exchange Capacity, exchangeable acids (H and Al) are high. The classification of Ultisol soil in the location of the Glealing Glean profile is Typic Hapludult, berliat, blend, isohipertermik.